2010
DOI: 10.1002/anie.200906988
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Thiostrepton Derivatives: Proteasome Inhibitors with a Dual Mode of Action

Abstract: Two birds, one stone: Semisynthetic derivatives of the ribosomal inhibitor thiostrepton display up to ten times higher antiplasmodial activity than the natural product itself. This activity was correlated with selective functional inhibition of the 20S proteasome. Thiostrepton derivatives are now established as novel antimalarials with a dual mode of action and highly promising scaffolds for proteasome inhibitor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 58 publications
5
81
0
1
Order By: Relevance
“…This interaction inhibits translation and also synthesis of the global gene expression regulator (p)ppGpp (40,41). Furthermore, thiostrepton inhibits the proteasome in eukaryotic cells (42,43) exerting antimalarial (44,45) and anticancer (42)(43)(44)(45)(46)(47) activities. Despite their unique mechanism of action and their high potency against pathogens such as methicillin-resistant Staphylococcus aureus and Enterococcus faecium or penicillin-resistant Streptococcus pneumonia (48), the clinical application of thiopeptides is impeded by their considerable size and low water solubility (35,(48)(49)(50)(51).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…This interaction inhibits translation and also synthesis of the global gene expression regulator (p)ppGpp (40,41). Furthermore, thiostrepton inhibits the proteasome in eukaryotic cells (42,43) exerting antimalarial (44,45) and anticancer (42)(43)(44)(45)(46)(47) activities. Despite their unique mechanism of action and their high potency against pathogens such as methicillin-resistant Staphylococcus aureus and Enterococcus faecium or penicillin-resistant Streptococcus pneumonia (48), the clinical application of thiopeptides is impeded by their considerable size and low water solubility (35,(48)(49)(50)(51).…”
Section: Significancementioning
confidence: 99%
“…Despite their unique mechanism of action and their high potency against pathogens such as methicillin-resistant Staphylococcus aureus and Enterococcus faecium or penicillin-resistant Streptococcus pneumonia (48), the clinical application of thiopeptides is impeded by their considerable size and low water solubility (35,(48)(49)(50)(51). However, recent progress in thiopeptide chemical synthesis (43,52), biosynthesis (53,54), and activity screens (55) may enable the development of new thiopeptide derivatives with improved pharmaceutical properties.…”
Section: Significancementioning
confidence: 99%
“…5 Bortezomib, the first FDA-approved proteasome inhibitor for use as a chemotherapeutic drug for cancer treatment, 6,7 is well characterized for its direct inhibition of two of three of the specific binding sites of the proteasome. 8 The thiazole antibiotic, thiostrepton, is a more recently discovered proteasome inhibitor which has been shown to inhibit the third site of the proteasome, 9 to result in cell death in a variety of cancer cell lines. 10,11 The allosteric effect of complementary proteasome inhibitors has been discussed, where the inhibition of the "caspase-like" site, the one inhibited by thiostrepton, can sensitize inhibition of the other "chymotrypsin-like" and "trypsin-like" sites by drugs such as bortezomib.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that thiopeptide-encoding sequences are widely distributed in the genomes of the human microbiota and contribute significantly to microbe-host interactions (4). In addition, it has been shown that thiopeptides have antimalarial (5) and antiproliferative activity in human cancers (6). Thus, there is considerable interest in the synthesis of thiopeptide variants to improve the pharmacological properties of naturally occurring thiopeptides for use in medicine, as well as to study their mechanism of action.…”
mentioning
confidence: 99%